Estudo da eficiência de coleta em Lavador Venturi com injeção de líquido por multi-orifícios - Ribeiro, Ana Paula Rodrigues Alves (Universidade Federal de São Carlos, 2005)
This work had for objective to study the influence of the variables liquid flow, throat length, number of orifices and gas velocity in the throat in the collection efficiency of a Venturi scrubber. As particulate matter to be removed from the gas, a phosphate concentrate of density 2.9 g/cm3 was used, fed at a mass flow rate of 3.16 g/min. The experimental system used in this work consisted of a Venturi scrubber of rectangular geometry operating horizontally, with liquid injection through 1 to 5 orifices with 1 diameter mm each, distributed in the scrubber throat. For the experiments, two experimental planning were used, with three factors in three different levels. In the first planning was studied the influence of the variables liquid flow in the range from 300 to 900 cm3/min, throat length in the range from 6.5 to 18.5 cm and number of orifices in the range from 1 to 5 holes; the gas velocity in the throat was kept constant at value of 69.33 m/s. In the second planning was studied the influence of the variable gas velocity in the throat in the range from 58.66 to 69.33 m/s, with the liquid injected by a single orifice. It was verified that the overall collection efficiency of the Venturi scrubber varied within the range from 50 to 91%, for the studied conditions in the first planning. A tendency of increase of the efficiency was observed with the increase of the liquid flow and of the throat length. As for the number of orifices, a better performance of the scrubber was verified when only 1 orifice was used. It was verified that the overall collection efficiency of the Venturi scrubber varied within the range from 52 to 93%, for the studied conditions in the second planning. Was observed that the increase in the gas velocity in the throat resulted in an increase in the overall collection efficiency. The predictions of the classical equations for collection efficiency of Johnstone et al. (1954), Calvert et al. (1972) and Leith and Cooper (1980) were compared to the experimental values. It was observed that both for the experimental results and for the models that the global efficiency increases with the increase of the liquid flow. However, it was verified that the models of Johnstone et al. and Calvert et al. underestimated the values of global efficiency obtained experimentally while the model of Leith and Cooper overestimated them. Therefore, it became necessary to adjust a model to the experimental points. It was taken as departure point the model of Calvert et al., for being a classic model and because it is widely used industrially. An adjustment equation for the empiric factor f using the experimental data was then performed. As it was verified in previous tests that the variable throat length is relevant in the collection efficiency and the same does not appear in the equation proposed by Calvert et al., it was decided to adjust an equation of f in function as a function of LG as f= 3005 , 0 . 5161 , 0 G L . The validity of the adjustment was verified by the good agreement of the experimental values of efficiency observed experimentally with the predicted values by the modified Calvert model.
Keywords: Ar - poluição; Coletas de partículas; Lavador Venturi; Limpeza de gases industriais; Air pollution; Venturi scrubber; Industrial gas cleaning; Particle collection; ENGENHARIAS::ENGENHARIA QUIMICA